The Henry Lewis Stimson diaries in the Yale University Library - Stimson, Henry L. (Henry Lewis), 1867-1950 (Manuscripts and Archives, Yale University Library, 1973)
Diaries, 1904-1945, documenting Stimson's interests and activities in a long life of public service.